2012
DOI: 10.1093/jncimonographs/lgs008
|View full text |Cite
|
Sign up to set email alerts
|

Introduction: Understanding and Influencing Multilevel Factors Across the Cancer Care Continuum

Abstract: Health care in the United States is notoriously expensive while often failing to deliver the care recommended in published guidelines. There is, therefore, a need to consider our approach to health-care delivery. Cancer care is a good example for consideration because it spans the continuum of health-care issues from primary prevention through long-term survival and end-of-life care. In this monograph, we emphasize that health-care delivery occurs in a multilevel system that includes organizations, teams, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
272
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(282 citation statements)
references
References 41 publications
2
272
0
Order By: Relevance
“…Furthermore, this review focused predominantly on broad research trends and gaps from the perspective of PCPs, thereby not addressing patient perspectives, social factors (e.g., racism), or healthcare system factors (e.g., clinical decision support) that can influence care delivery. 81 This review did not focus on how provider characteristics (e.g., training, age) may contribute to differences in the outcomes of interest; future research could explore such differences. Finally, this review does not offer insight into PCPs' experiences with novel applications of genomic testing currently being introduced into cancer care (e.g., multi-gene panel testing, although a reviewed article noted that 42% of providers have ordered such testing 39 ).…”
Section: Limitationsmentioning
confidence: 99%
“…Furthermore, this review focused predominantly on broad research trends and gaps from the perspective of PCPs, thereby not addressing patient perspectives, social factors (e.g., racism), or healthcare system factors (e.g., clinical decision support) that can influence care delivery. 81 This review did not focus on how provider characteristics (e.g., training, age) may contribute to differences in the outcomes of interest; future research could explore such differences. Finally, this review does not offer insight into PCPs' experiences with novel applications of genomic testing currently being introduced into cancer care (e.g., multi-gene panel testing, although a reviewed article noted that 42% of providers have ordered such testing 39 ).…”
Section: Limitationsmentioning
confidence: 99%
“…A number of studies revealed a fragmented delivery care system (Bourjolly, Hirschman, & Zieber, 2004) and barriers to communication (Tapin et al, 2012). Given that many AABCS embodied and embraced the definition and meaning of survivorship and the resulting themes (altruism, spirituality, resilience, and thriving), they appear to be well equipped and should be sought for the role of Survivor's Navigators.…”
Section: Implications For Practice and Conclusionmentioning
confidence: 99%
“…Conceptual models of cancer screening identify a role for risk assessment and communication between providers and patients as important aspects of effective screening processes. [4][5][6][7] Prior studies indicate that the adoption of system-based strategies such as health information technology (HIT) and decision support improves the quality of primary care delivery, including uptake of cancer screening. [8][9][10] However, they also report a lack of HIT and practice-based systems to support screening in primary care.…”
Section: Introductionmentioning
confidence: 99%